Design and performance analysis of Rectenna Circuit - El Batal, K.; Chakhchaoui, N.; Eddiai, A.; Meddad, M.; Rguiti, M.; Mazroui, M.; Cherkaoui, O. (IOP conference series. Materials Science and Engineering, 2020)
Radio Frequency Energy harvesting is an extremely important research subject, linked to sustainability, and could be a potential solution to conventional energy supplies. The main idea is to develop battery-free wireless sensors able to capture the available energy into the mentioned bandwidth. In this paper, a 1.8-2.4 GHz wideband rectenna is designed for radio frequency (RF) energy harvesting in the context of wireless sensor nodes (WSN). For this purpose, the agilent Advanced Design System (ADS) was used. This article presents the design and simulation of a high output voltage rectifier. First, we designed a rectifier based on Metelics MSS20-141 Schottky diode using a series topology to convert electromagnetic energy into DC. Then, a low-pass filter was implemented to filter out undesirable harmonics generated by the non-linear Schottky diode. Simulation results show that load resistance, input frequency and input power are important parameters to evaluate the performances of RF energy harvester. Also, the three RF bands, GSM1800, UMTS and Wi-Fi, are considered. Therefore, the designed system has an average RF-to-DC conversion of 18 % for an incident power of -10 dBm for a variation of 20 to 1200 Ω.